Acute respiratory distress syndrome due to Clostridium difficile colitis: a case report and review of the literature - Donet, Jean A. (2017)
Clostridium difficile is a major cause of antibiotic-associated diarrhea. We report a patient with complicated Clostridium difficile infection (CDI) who developed rapidly progressive acute respiratory distress syndrome (ARDS), for which CDI was the only identifiable source. CDI should be considered in the differential diagnosis for anyone with diarrhea who presents ARDS, especially in high-risk groups such as the elderly, hospitalized patients, or those who have had a history of CDI.